Three amino acid residues are required for the recognition of Ralstonia solanacearum RipTPS in Nicotiana tabacum - An, Yuyan; Chen, Jialan; Xu, Zhangyan; Ouyang, Xue; Cao, Peng; Wang, Rongbo; Liu, Peiqing; Zhang, Meixiang (Frontiers in Plant Science, 2022)
Ralstonia solanacearum causes devastating diseases in a wide range of economically important crops. It secretes a large number of virulence factors, also known as effectors, to promote its infection, and some of them are recognized when the host plant contains corresponding resistance genes. In this study we showed that a type III effector RipTPS from the avirulent R. solanacearum strain GMI1000 (RipTPSG) specifically induced cell death in Nicotiana tabacum, but not in Nicotiana benthamiana, whereas the RipTPS homolog in the virulent strain CQPS-1 (RipTPSC) induced cell death in neither N. tabacum nor N. benthamiana. These results indicated that RipTPSG is recognized in N. tabacum. Expression of RipTPSG induced upregulation of hypersensitive response (HR) -related genes in N. tabacum. The virulence of CQPS-1 was reduced when RipTPSG was genetically introduced into CQPS-1, further confirming that RipTPSG functions as an avirulence determinant. Protein sequence alignment indicated that there are only three amino acid polymorphisms between RipTPSG and RipTPSC. Site-directed mutagenesis analyses confirmed that the three amino acid residues are jointly required for the recognition of RipTPSG in N. tabacum. Expression of either RipTPSG or RipTPSC suppressed flg22-triggered reactive oxygen species (ROS) burst in N. benthamiana, suggesting that RipTPS contributes to pathogen virulence. Mutating the conserved residues in RipTPS’s trehalose-phosphate synthase (TPS) domain did not block its HR induction and defense suppression activity, indicating that the TPS activity is not required for RipTPS’s avirulence and virulence function.